La incorporación de los presupuestos de los procesos estructurales por el Supremo Tribunal Federal en el juicio de litigios estructurales - Hennig Leal, Mônia Clarissa (2024)
The study examines the incorporation of the premises of structural litigation theory by the Brazilian Federal Supreme Court (STF) in decisions under monitoring by the Center for Complex Structural Litigation - Nupec (ADPFs 347, 635, and 709). Adopting a deductive approach and an analytical procedural method, theoretical contributions related to disputes, processes, and structural decisions are initially addressed, including a list of the premises of structural process theory. The article explores the internal restructurings that the Brazilian Federal Supreme Court has implemented to adjust judicial procedures to handle structural disputes in the absence of regulation on structural processes in Brazil. Finally, based on the premises of structural processes identified at the beginning of the study, the contents of Brazilian Federal Supreme Court decisions are analyzed, with the aim of verifying whether they incorporate the elements of structural processes. We conclude that the three decisions analyzed incorporate a dialogical perspective (both between institutions and between the parties involved and the state), prioritize the participation of affected groups in the formulation of fair and effective decisions, apply an experimentalist approach, apply mechanisms for monitoring the implementation and effectiveness of the decision, and, on some occasions, involve a legal-cultural translation of structural experiences and remedies from other countries by learning from similar cases judged by courts elsewhere and adapting those standards to the Brazilian context.